Fast-bactericidal effect of polyion complex nanoparticles on Gram-negative bacteria - Wei, Guangmin (2020)
There is an urgent need for effective bactericidal agents for use in real commercial formulations because many old disinfectants, such as halogenated compounds, are now banned. Cationic polymers may have good bactericidal properties in pure water or buffer but typically become ineffective in the presence of anionic surfactants that are widely used in many commercial formulations. Here, we discover that polyion complex (PIC) nanoparticles formed by cationic polymers of poly[3-(acrylamido)propyl]trimethylammonium chloride (PAMPTMA) in the presence of anionic surfactants display a promising fast-bactericidal effect (>99.99% killing within a 10 min treatment) on Gram-negative Escherichia coli (ATCC 8739). To examine the influence of the hydrophobicity on the bactericidal property, we synthesize PAMPTMA-b-poly(butyl methacrylate) and discover that increasing the hydrophobicity has little influence on the bactericidal property of PIC nanoparticles. A mechanism study shows that cationic PIC nanoparticles rapidly cause significant pores in both the outer and inner membranes because of their large size and high local concentration of positive charges. Rapid membrane pore formation results in fast cell death. The discovery—certain cationic polymers when formulated with anionic surfactants are even more bactericidal than neat cationic polymers alone—paves the way for potential applications of synthetic cationic polymers in commercial formulations.